2019
DOI: 10.21608/ajbs.2019.72270
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity among some fennel cultivars (Foeniculum vulgare Mill.) by ISSR and SCoT Markers

Abstract: Fennel (Family Apiaceeae) is one of those strategic medicinal and aromatic plants in Egypt with great value as an economical exported plant. Fennel undergoes propagation through breeding of some fennel cultivars from different world region in order to keep out of genetic deterioration in the native Egyptian cultivars, and enrich its favorable active ingredients. The advanced plant breeding programs depend on some markers such as morphological, cytological, biochemical and molecular markers to study its genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
2
Order By: Relevance
“…They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants. While this result disagrees with Ramadan et al (2019), who found that the ISSR marker is more discriminating and provides more informative data than SCoT in fennel cultivars.…”
Section: Molecular Assessmentcontrasting
confidence: 97%
“…They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants. While this result disagrees with Ramadan et al (2019), who found that the ISSR marker is more discriminating and provides more informative data than SCoT in fennel cultivars.…”
Section: Molecular Assessmentcontrasting
confidence: 97%
“…They found that the SCoT marker was more informative and effective than the ISSR marker to estimate the genetic diversity and perform fingerprinting in these plants. While this result disagrees with Ramadan et al (2019), who found that the ISSR marker is more discriminating and provides more informative data than SCoT in fennel cultivars. While Baghizadeha and Dehghan (2018) and other researchers recommended that it is preferable to use these molecular marker techniques in combination with each other for distinctive fingerprinting.…”
Section: Resulted Data Comparison Of Discriminating Capacity Between ...contrasting
confidence: 97%
“…With the primer RMN-P3, the PIC of RAPD was 0.37 and the minimum PIC value of 0.15 was recorded with the OP-B18 primer with ISSR; the highest PIC record was 0.30 for primers UBC-812 and UBC-814, while the lowest was 0.0 for the primer UBC-810, with an average of 0.25. Ramadan et al [17] found more discriminating results with the ISSR marker than the SCoT marker among fennel cultivars. RAPD was also found to be an effective tool in detecting genetic diversity in peanut cultivars [18].…”
Section: Genetic Variations Revealed By Rapd and Issr Analysismentioning
confidence: 97%
“…Ismailia-1 contained large oil bodies with D50 of 6.7 µm. The number of existing oil bodies in a slide measurement indicated the difference in abundance among cultivars (17,59 and 63% in Ismailia-1, Samnut-26 and NC-7, respectively). Samnut-22 and Ex-Dakar had a higher abundance (82 and 80%, respectively) (Table 8).…”
Section: Size and Number Of Oil Bodiesmentioning
confidence: 99%
See 1 more Smart Citation